2015
DOI: 10.1186/s12984-015-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-selected gait speed - over ground versus self-paced treadmill walking, a solution for a paradox

Abstract: BackgroundThe study of gait at self-selected speed is important. Traditional gait laboratories being relatively limited in space provide insufficient path length, while treadmill (TM) walking compromises natural gait by imposing speed variables. Self-paced (SP) walking can be realized on TM using feedback-controlled belt speed. We compared over ground walking vs. SP TM in two self-selected gait speed experiments: without visual flow, and while subjects were immersed in a virtual reality (VR) environment induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…Other key differences between treadmill and outdoor running involve alterations to gait and other biomechanical factors (Hanley & Mohan, 2014), along with pace being AFFECTIVE OUTCOMES OF DIFFERENT EXERCISE SETTINGS 14 controlled mechanically versus spontaneously (Plotnik, Azrad, Bondi, Bahat, Gimmon, Zeilig, et al, 2015). Additionally, there are major differences between these conditions in optic flow (sense of movement related to visual sensations).…”
Section: Discussionmentioning
confidence: 99%
“…Other key differences between treadmill and outdoor running involve alterations to gait and other biomechanical factors (Hanley & Mohan, 2014), along with pace being AFFECTIVE OUTCOMES OF DIFFERENT EXERCISE SETTINGS 14 controlled mechanically versus spontaneously (Plotnik, Azrad, Bondi, Bahat, Gimmon, Zeilig, et al, 2015). Additionally, there are major differences between these conditions in optic flow (sense of movement related to visual sensations).…”
Section: Discussionmentioning
confidence: 99%
“…One potential limitation was related to measuring self-paced gait speed and variability while subjects walked on a treadmill. Yet, it has been demonstrated that self-paced treadmill walking provides a reliable record of typical self-paced gait speed [49], and that variability measured by treadmill walking may be an acceptable representation of over-ground walking [50]. It should also be noted that as all subjects were measured under the same conditions, it could be expected that the same differences would be observed in over-ground walking.…”
Section: Discussionmentioning
confidence: 99%
“…The treadmill was operated in self-paced mode, in which the motor is operated as a function of the instantaneous position and speed of the participant, which are sampled using a motion capture system (see more details in [20]).…”
Section: Self-paced Walking Modementioning
confidence: 99%